THE USE OF NOUN PHRASE IN ENGLISH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explains how noun phrases are used in English. A noun phrase is a group of words built around a main noun, often including words like determiners, adjectives, or other modifiers. Noun phrases can act as subjects, objects, or complements in sentences, helping speakers and writers give clear and detailed information. The article gives simple examples from everyday and academic English and shows why noun phrases are important for making communication precise, smooth, and easy to understand. Understanding how to use noun phrases is useful for students, writers, and anyone learning English.